Kerkwees in die saeculum vandag, Deel 1: Eenheid te midde van veelheid - Van Wyk, Tanya ca. 20./21. Jh. (HTS teologiese studies, 2012)
Being church in the saeculum today, Part 1: Unity through plurality. From a narrative theological perspective, the article tells the story of the church which has always been characterised by a tension between unity and plurality. The article illustrates that the root of the tension can be found in a binary mentality which traps the church in an endless labyrinth and keeps the it from being ‘A Broad Place’, a ’wide open space’. The article suggests that re-telling the church’s grand narrative of the Trinity sustains the re-telling of the church’s narrative in the changing environment of a secular society.